A POTENTIAL FOR CAUSALITY IN DEVELOPMENT COUNTRIES (TRACKING E-PARTICIPATION AND E-GOVERNMENT IN SOUTHEAST ASIAN COUNTRIES) - George Towar Ikbal Tawakkal (Universitas Muhammadiyah Jember, 2022)
Many countries have democratized by utilizing information and communication technology as e-government. Conceptually, e-government should increase participation which is equally called e-participation. Several studies confirm and reject this assumption. Some claim that there is no causal relationship between e-government development and e-participation progress. Continuing the debate, this article addresses how often the development of e-government is in line with the progress of e-participation. What pattern appears in the relationship between the two variables? Based on data provided by UNDP in EDGI and EPI scores, this article looks at Indonesia and other Southeast Asian countries that directly border Indonesia; Malaysia, Singapore, Brunei Darussalam, and Timor Leste. A series of categories are defined to facilitate analysis, such as low, moderate, and high fluctuations for EDGI and EPI respectively, then low, moderate, and high consistency and inconsistency for the confluence of EDGI and EPI. Taking into account the national income per capita of these countries, it is known that the potential for causality is more likely to occur in developed countries that have high national income per capita.